Strategi Manajemen Kepala Desa dalam Mengembangkan UMKM terhadap Kesejahteraan Masyarakat di Desa Rensing: Strategic Management of Village Heads in Developing Micro, Small and Medium Enterprises (MSMEs) for Community Welfare in Rensing Village - Lalu. A. Hery Qusyairi; Abdurrahim; Nur Asiah Jamil; Azwariadi; Baiq Juliani (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2026)
Economic activities aim to increase the power and standard of living of the community, because the community's needs will be met along with economic growth. This study aims to analyze the strategic management of the village head in developing Micro, Small, and Medium Enterprises (MSMEs) and its impact on improving the welfare of the community in Rensing Village. The main focus of this study is on the village head's strategy in planning, organizing, driving, and supervising MSME development programs. This study uses a qualitative approach with data collection methods through interviews, observation, and documentation. The main informants in this study consist of the Head of Rensing Village, the Village Secretary, and the Community. Data are analyzed descriptively through the stages of data reduction, and drawing conclusions. The results of this study indicate that the strategic management carried out by the village head in developing MSMEs in Rensing Village shows the existence of targeted planning and actions, improving the welfare of the community in the village is the main goal that can be achieved through various integrated approaches, both from economic, social, educational, health, and community participation aspects, Village Head Methods in Increasing Community Awareness and Participation in MSME Development. In increasing community awareness and participation, the village head uses a persuasive and educational approach, such as holding regular training, inviting the community to village meetings, and providing real examples of MSME success.